2020
DOI: 10.2174/1874434602014010092
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Self-Efficacy as Predictors of Academic Satisfaction among Nursing Students

Abstract: Background: number of factors contribute to psychological disturbances among university students. Most important, such psychological factors may influence their academic satisfaction that associates with their performance. Purpose: To examine prediction power of academic stress and academic self-efficacy on academic satisfaction among nursing students. Methods: A convenience sample of 117 nursing students recruited from two n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 19 publications
2
19
0
6
Order By: Relevance
“…This has been sustained by Shehadeh et al (2020) who reported that students were able to identify sources of anxiety that are related to their academic requirements and assignments. Students were aware about their capabilities and did connect their anxiety to their academic self-efficacy in which being able to perform the academic task is associated with lower level of anxiety.…”
Section: Discussionmentioning
confidence: 93%
“…This has been sustained by Shehadeh et al (2020) who reported that students were able to identify sources of anxiety that are related to their academic requirements and assignments. Students were aware about their capabilities and did connect their anxiety to their academic self-efficacy in which being able to perform the academic task is associated with lower level of anxiety.…”
Section: Discussionmentioning
confidence: 93%
“…This may psychologically burden families and students. In addition, and during the pandemic of COVID-19, students and their families suffered economic, social, and psychological hardships that compromise their ability to manage their biopsychosocial needs, many findings observed in other studies of university students with similar public health restrictions and online education challenges (Shehadeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, drug and alcohol abuse is considered a symptom of wounded spirituality [24] . This view is not what Royce [25] went for when he called addiction, to alcohol and any other drug, as a spiritual disease. Royce [25] maintained that addiction is simply not functioning with ease regarding the drug.…”
Section: Spirituality and Alcoholismmentioning
confidence: 96%
“…This view is not what Royce [25] went for when he called addiction, to alcohol and any other drug, as a spiritual disease. Royce [25] maintained that addiction is simply not functioning with ease regarding the drug. He relied mainly on his understanding of the word disease.…”
Section: Spirituality and Alcoholismmentioning
confidence: 96%